КУЗМАН ШАПКАРЕВ КАКО КРИТИЧАР И ПОЛЕМИЧАР (по повод 190 години од неговото раѓање) - Славчо Ковилоски (My University, 2024)
This text refers to the critical-essayistic texts of Kuzman Shapkarev. He was publishing the texts in several newspapers and magazines: Zbornik na Narodni Umotvorbi, Nauka i Kniznina, Periodichesko Spisanie, Novini, Svetlina, etc. In periodicals, he published numerous critical reviews on books and articles, with versatile content: folk-ecclesiastical, linguistic, didactic, descriptive, ethnographic and political. Shapkarev appears as one of the first biographers and critics of the life and work of the Miladinov brothers. According to the quantity of the works written, Shapkarev can be included among the most prolific and active Macedonian critics of the 19th century who carefully followed periodicals and published in them as well.
Keywords: Kuzman Shapkarev, Macedonian literary criticism in the 19th century, critic, biographer, the Miladinov brothers.